2022
DOI: 10.1007/s00704-021-03883-8
|View full text |Cite
|
Sign up to set email alerts
|

A new regionalization of rainfall patterns based on wavelet transform information and hierarchical cluster analysis in northeastern Algeria

Abstract: Availability of data and material:The datasets generated during and/or analysed during the current study are available from the corresponding author on reasonable request.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…The significance of applied climatology increased after World War II, with numerous studies being published addressing the direct impacts of climate [ 2 , 3 ]. Knowledge of rainfall data and characteristics is indispensable for water planning and management [ [4] , [5] , [6] , [7] ]. Several studies have assessed the spatiotemporal rainfall change and variability worldwide [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of applied climatology increased after World War II, with numerous studies being published addressing the direct impacts of climate [ 2 , 3 ]. Knowledge of rainfall data and characteristics is indispensable for water planning and management [ [4] , [5] , [6] , [7] ]. Several studies have assessed the spatiotemporal rainfall change and variability worldwide [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%
“…Various hydrology and water resource-related disciplines have recently shown an increased interest in using wavelet analysis. Particularly in terms of periodicity, numerous research studies have demonstrated that wavelet analysis is a useful tool for characterizing and analyzing climatic and hydrological data [22][23][24][25][26][27][28][29][30][31], and, also, the frequency domain variable structures of various climatic or hydrological variables can be examined and synthesized using wavelet analysis, which is also an effective method for exploring relationships between them [32][33][34][35][36][37][38][39][40][41]. Recent research has shown that wavelet analysis is an effective technique for identifying irregularly distributed multiscale characteristics in hydrometeorological data, and, also, the ability to establish quantitative correlations between various observation series using wavelet-based expressions has been demonstrated [42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Annual global precipitation increased gradually from 1900 to the late 1950s, decreased until 1970, increased in the 1970s, and decreased after 1980. According to previous evaluations, the rainfall patterns study and investigation have become a more active research issue for better regional water resources and hazards management in recent years (Zerouali et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…DWT and CWT wavelet transform techniques have been used successfully in many applications, including transient image and signal analysis and processing and communication systems (Chandrasekhar and Eswara Rao 2012;Galiana-Merino et al 2013;Hill and Uvarova 2018). Wavelet transform is an excellent way to analyze nonstationary signals in nature (Zerouali et al 2022;Sang et al 2013). CWT and DWT are two procedures of wavelet transform (Brassarote et al 2018;Rhif et al 2019;Adhikari et al 2020).…”
Section: Introductionmentioning
confidence: 99%